Internet of Things (IoT) Based Trash Can Monitoring System Using Web Services with the CodeIgniter Framework in the Surabaya Aviation Polytechnic Environment - Irfansyah, Ade; Thiro Kabul Yunior, Yudhis; Bagus Harianto, Bambang (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
The use of plastic bottles tends to increase every year. Plastic bottles have now become a daily necessity and more and more plastic bottle products are being used. This has an impact on the accumulation of plastic bottle waste in rubbish dumps in the Surabaya Aviation Polytechnic environment. Plastic bottle waste is one of the problems that must be resolved because it is difficult for the soil to decompose and can cause environmental pollution in the Surabaya Aviation Polytechnic Environment. Based on the background of these problems, Innovation and Research in Management of plastic waste processing is needed at the Surabaya Aviation Polytechnic campus by developing new technology and strategies to recycle or manage plastic waste more efficiently and environmentally friendly. In this research we propose the title Based Waste Bin Monitoring System Internet of Things (IoT) Using Web Services with the CodeIgniter Framework in the Surabaya Aviation Polytechnic Environment. The flow of this research is to build an Internet of Things platform for monitoring plastic bottle waste using web services with the CodeIgniter framework method so that it can be integrated into the data management system. The results of this waste monitoring will later be integrated into an Android-based cellphone application so that it can be monitored in real time. The results from plastic bottle waste will later be passed on for recycling.